DPAGT1‐Mediated Protein N‐Glycosylation Is Indispensable for Oocyte and Follicle Development in Mice - Li, Hui (Adv Sci (Weinh), 2020)
Post‐translational modification of proteins by N‐linked glycosylation is crucial for many life processes. However, the exact contribution of N‐glycosylation to mammalian female reproduction remains largely undefined. Here, DPAGT1, the enzyme that catalyzes the first step of protein N‐glycosylation, is identified to be indispensable for oocyte development in mice. Dpagt1 missense mutation (c. 497A>G; p. Asp166Gly) causes female subfertility without grossly affecting other functions. Mutant females ovulate fewer eggs owing to defective development of growing follicles. Mutant oocytes have a thin and fragile zona pellucida (ZP) due to the reduction in glycosylation of ZP proteins, and display poor developmental competence after fertilization in vitro. Moreover, completion of the first meiosis is accelerated in mutant oocytes, which is coincident with the elevation of aneuploidy. Mechanistically, transcriptomic analysis reveals the downregulation of a number of transcripts essential for oocyte meiotic progression and preimplantation development (e.g., Pttgt1, Esco2, Orc6, and Npm2) in mutant oocytes, which could account for the defects observed. Furthermore, conditional knockout of Dpagt1 in oocytes recapitulates the phenotypes observed in Dpagt1 mutant females, and causes complete infertility. Taken together, these data indicate that protein N‐glycosylation in oocytes is essential for female fertility in mammals by specific control of oocyte development.